DC bus stabilization using passive damping network in distributed power system with constant power load - Awang Bin Jusoh; Mohamad Hamka Bin Saiful; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
In distributed power system (DPS), the stability performance is always associated with the behaviour of constant power load (CPL). Since DPS large complex system build up from many power electronic converters, the DC bus of the system becomes unstable due to the strenuous action from power converters. When these converters tightly regulated, it behaves as constant power load and exhibit negative incremental input impedance which becomes the main reason in stability degradation of DPS. In this paper, four passive damping network topologies was proposed to reduce the DC bus instability. The best damping performance of the topologies was chosen and analysed using MATLAB/Simulink. The DC bus performances was studied in four cases which are damping behavior due to CPL power level, CPL disconnection, effects of filter and damping capacitor, and effects of filter cut-off frequency. Simulation results obtained shows that the DC bus was successfully stabilized and the resonance damped when passive damper installed. An experimental hardware tests was conducted to verify the proposed damping method and the results were compared with the simulated output waveforms. The analysis results in overshoot, settling time and steady state error of bus voltage shows system improvement with the proposed damper network.